2018
DOI: 10.1007/s00198-018-4499-4
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis uncovers monogenic bone disorders in women with pregnancy-associated osteoporosis: three novel mutations in LRP5, COL1A1, and COL1A2

Abstract: Our data show that previously unrecognized monogenic bone disorders play an important role in PAO. Pregnancy should be considered a skeletal risk factor, which can promote the initial clinical onset of such skeletal disorders. The underlying increased calcium demand is essential in terms of prophylactic and therapeutic measures, which are especially required in individuals with a genetically determined low bone mass. The implementation of this knowledge in clinical practice can enable the partial recovery of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 43 publications
(53 reference statements)
0
29
0
Order By: Relevance
“…The significant finding of low bone turnover, both in terms of serum markers and at the tissue level, should be viewed in this context. We acknowledge that we can never be certain that all women were assessed at their baseline bone remodeling status, and moreover, that it is possible that some women with PLO have a different or longer trajectory of bone remodeling and BMD change postpartum than normal healthy women . However, if postpartum bone remodeling changes were extended in PLO women, we would expect them to have higher rather than lower bone remodeling parameters compared to other groups.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The significant finding of low bone turnover, both in terms of serum markers and at the tissue level, should be viewed in this context. We acknowledge that we can never be certain that all women were assessed at their baseline bone remodeling status, and moreover, that it is possible that some women with PLO have a different or longer trajectory of bone remodeling and BMD change postpartum than normal healthy women . However, if postpartum bone remodeling changes were extended in PLO women, we would expect them to have higher rather than lower bone remodeling parameters compared to other groups.…”
Section: Discussionmentioning
confidence: 97%
“…We acknowledge that we can never be certain that all women were assessed at their baseline bone remodeling status, and moreover, that it is possible that some women with PLO have a different or longer trajectory of bone remodeling and BMD change postpartum than normal healthy women. (45) However, if postpartum bone remodeling changes were extended in PLO women, we would expect them to have higher rather than lower bone remodeling parameters compared to other groups. We believe that our finding of low bone remodeling, unexpected at any postpartum time point, is of mechanistic interest.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…Bone microstructure of the patients with detected ENPP1 mutation was further analyzed using high-resolution peripheral quantitative computed tomography (HR-pQCT; XtremeCT, Scanco Medical, Bruttisellen, Switzerland) at the nondominant distal radius and tibia in a standardized procedure as previously described using the in vivo protocol. (24,26) Bone geometric parameters included cortical bone area (Ct. bone area, mm 2 ) and trabecular bone area (Tb. bone area, mm 2 ); volumetric bone mineral density (vBMD) measurements included total vBMD (total BMD, mgHA/cm 3 ), cortical BMD (Ct.BMD, mgHA/cm 3 ), and trabecular BMD (Tb.BMD, mgHA/cm 3 ).…”
Section: Assessment Of Bone Metabolism and Skeletal Status In Humansmentioning
confidence: 99%
“…Some researches [4,5] have shown that mothers of PLO patients have a higher incidence of fractures and the children of PLO patients have a lower bone mass than the general population, suggesting that PLO is genetically related. Butscheidt, S et al [6] detected some new mutations in LRP5, COL1A1 and COL1A2 genes in 7 patients with PLO, which played an important role in the occurrence and development of Pregnancy and lactation-associated osteoporosis.…”
Section: Discussionmentioning
confidence: 99%